Strategi Humas Palang Merah Indonesia Dalam Meningkatkan Kesadaran Masyarakat Untuk Donor Darah Sukarela Di Kabupaten Banggai - Sari, Devi Novita Indah; Suasa; Farista, Gita (JPS: Journal of Publicness Studies, 2025)
This study aims to explore the "Public Relations Strategy of PMI Banggai Regency in Increasing Public Awareness for Voluntary Blood Donation". The research is descriptive in nature, with a qualitative approach. Data collection techniques include observation, interviews, and documentation to gather primary and secondary data, which are analyzed using SWOT analysis. This study uses Kotten's theory as cited in Salusu (2006; 104-105), Corporate Strategy, Program Strategy, Resource Support Strategy, and Institutional Strategy). The study involves 10 informants. The results of the study indicate that the public relations strategy implemented by PMI Banggai Regency has successfully increased public awareness, especially through collaboration with various stakeholders and social media. However, challenges remain, particularly among the younger generation. To further enhance awareness, corporate development strategy should be the main focus. Strengthening collaborations with government agencies, the private sector, educational institutions, and expanding networks to the village level can help reach a broader population. Additionally, innovation in educational approaches is necessary to attract attention and deepen the community's understanding of the importance of voluntary blood donation.